Brain-powered science teaching and learning with discrepant events - O'Brien, Thomas 1956- (NSTA Press, 2010)
"Author Thomas O'Brien takes these and 30 more science inquiry activities to a higher level in this book for educators who love to surprise and challenge their students with unanticipated results. Using experiments based on the science of a "discrepant event"?an experiment or demonstration in which the outcome is not what students expect?O?Brien shows how learners can be motivated to reconsider their preconceived notions and think more closely about what has actually occurred and the underlying scientific explanations."--Publisher's description.